2009
DOI: 10.1371/journal.pone.0005080
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Societal Health Quality Lost to Tuberculosis

Abstract: BackgroundIn developed countries, tuberculosis is considered a disease with little loss of Quality-Adjusted Life Years (QALYs). Tuberculosis treatment is predominantly ambulatory and death from tuberculosis is rare. Research has shown that there are chronic pulmonary sequelae in a majority of patients who have completed treatment for pulmonary tuberculosis (PTB). This and other health effects of tuberculosis have not been considered in QALY calculations. Consequently both the burden of tuberculosis on the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…In Texas, a case of TB was calculated to cost 1.4 QALYs (see Glossary) [49]. In the UK, each case of human bTB is likely to cost similar numbers of QALYs or DALYs.…”
Section: Box 2 Health Economics Of Btb Controlmentioning
confidence: 99%
“…In Texas, a case of TB was calculated to cost 1.4 QALYs (see Glossary) [49]. In the UK, each case of human bTB is likely to cost similar numbers of QALYs or DALYs.…”
Section: Box 2 Health Economics Of Btb Controlmentioning
confidence: 99%
“…Studies showed that as compared with the general population, TB patients reported reductions in their physical health, psychological health, and social functioning23. There are several aspects of TB that may lead to deficits in HRQL, like social stigma, prolonged therapy, potentially toxic drugs, lack of knowledge regarding the disease and its treatment, anxiety, and depression4567.…”
Section: Introductionmentioning
confidence: 99%
“…With 1.3 million TB deaths (including TB deaths in HIV-positive individuals) in 2012 (WHO 2013a), TB and the human immunodeficiency virus (HIV) are the top causes of death from a single infectious agent worldwide (Lozano et al 2012;Ortblad et al 2013). TB is a leading killer among adults in the most economically productive age groups and people living with HIV (Lopez et al 2006), and even those cured from TB can be left with lifetime sequelae that substantially reduce their quality of life (Miller et al 2009). Recognition of these facts has kept TB control high on the international public health agenda since the early 1990s (Zumla et al 2009;Lienhardt et al 2012a), following years of neglect during the 1980s (Raviglione and Pio 2002).…”
mentioning
confidence: 99%